Early orthodontic/orthopedic treatment in patients with class II sagittal anomalies. A review. - Yanez-Zurita, Christian (2023)
Introduction: Class II sagittal anomalies have a prevalence of between 18-32% of the population. To resolve this type of malocclusion, various therapies have been proposed, some of which involve functional orthodontic or orthopedic appliances. However, it is still a matter of discussion whether the treatments should be started at an early age in patients, or if there are adverse effects that could harm structures of the stomatognathic system. Objective: To analyze the results obtained from early treatment in patients with Class II sagittal malocclusion through a literature review. Materials and methods: An advanced search with terms and connectors was carried out in the Medline via Pubmed and Science Direct databases. Inclusion and exclusion criteria were applied for the definitive selection. Results: Through this search, a total of 5909 articles were collected, of which 23 were considered to meet the criteria established in this review work. Conclusions: There are orthodontic/orthopedic devices aimed at solving the characteristics of class II sagittal malocclusions, but before planning early treatment it is essential to provide an accurate diagnosis to evaluate the specific type of appliance that is required.